Internalization of Religious Moderation Values in Islamic Religious Education Instruction in Secondary Schools - Yana Mulyana; Acip Acip; Budi Munawar Khutomi; Solahudin Solahudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the implementation of strengthening religious moderation character through Islamic Religious Education (PAI) instruction for students at SMAN 1 Palabuhanratu. The study employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, involving PAI teachers, Muslim students, and non-Muslim students as sources of information. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that the strengthening of religious moderation character is carried out by integrating values such as national commitment, tolerance, opposition to radicalism and violence, and acceptance of local culture into PAI instruction and school culture. Students demonstrated attitudes of respecting religious and opinion differences, maintaining unity, participating in national activities, and resolving issues through deliberation. PAI teachers played a crucial role through role-modeling, contextual learning, dialogue, and the fostering of socio-religious habits. These findings confirm that PAI instruction can serve as a strategic vehicle for shaping students into individuals who are religious, tolerant, peace-loving, and capable of living harmoniously amidst diversity.